Spireoside Controls Blast Disease by Disrupting Membrane Integrity of Magnaporthe oryzae - Xu Liting; He Kaiwei; Guo Chunyu; Quan Cantao; Ma Yahuan; Zhang Wei; Ren Lifen; Wang Long; Song Li; Ouyang Qing; Yin Junjie; Zhu Xiaobo; et al. (Rice Science)
The application of fungicides is an effective strategy for controlling plant diseases. Among these agents, plant-derived antifungal metabolites are particularly promising due to their eco-friendly and sustainable nature. Plant secondary metabolites typically exhibit broad-spectrum antifungal activity without selective toxicity against pathogens. However, only a small fraction of antifungal metabolites have been identified from the tens of thousands of known plant secondary metabolites. In this study, we conducted a metabolomic analysis on both blast-resistant (Digu) and -susceptible (Lijiangxintuanheigu) rice varieties to uncover novel metabolites that enhance blast resistance. We found that 24 and 48 h post-inoculation with Magnaporthe oryzae were critical time points for metabolomic profiling, based on the infected status of M. oryzae in rice and the observed differences in shikimate accumulation between the two varieties. Following metabolomic analysis, we identified nine flavonoids that were differentially accumulated and are considered potential candidates for disease control. Among these, apigenin-7-glucoside, rhamnetin, and spireoside were found to be effective in controlling blast disease, with spireoside demonstrating the most pronounced efficacy. We discovered that spireoside controlled blast disease by inhibiting both spore germination and appressorium formation in M. oryzae, primarily through disrupting cell membrane integrity. However, spireoside did not induce rice immunity. Furthermore, spireoside was also effective in controlling sheath blight disease. Thus, spireoside shows considerable promise as a candidate for the development of a fungicide for controlling plant diseases.